2011
DOI: 10.1038/gt.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of rAAV vector and plasmid DNA in blood after intramuscular injection in nonhuman primates: implications for gene doping

Abstract: Legitimate uses of gene transfer technology can benefit from sensitive detection methods to determine vector biodistribution in pre-clinical studies and in human clinical trials, and similar methods can detect illegitimate gene transfer to provide sports-governing bodies with the ability to maintain fairness. Real-time PCR assays were developed to detect a performance-enhancing transgene (erythropoietin, EPO) and backbone sequences in the presence of endogenous cellular sequences. In addition to developing rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 44 publications
4
83
0
Order By: Relevance
“…This relates to a very recent report demonstrating that intramuscularly injected conventional plasmid is rapidly eliminated (Ni et al 2011). Equally we noted that the signal for exogenous FAK was importantly reduced in transfected soleus muscle 7 days after transfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relates to a very recent report demonstrating that intramuscularly injected conventional plasmid is rapidly eliminated (Ni et al 2011). Equally we noted that the signal for exogenous FAK was importantly reduced in transfected soleus muscle 7 days after transfection.…”
Section: Discussionmentioning
confidence: 99%
“…While the detection of genetic modiWcation has been shown for virus-mediated transfection of skeletal muscle with expression construct for the secreted hematopoietic factor erythropoietin (Beiter et al 2011;Ni et al 2011) it is unlikely that this transfection technology would be a method of choice. This is explained by various drawbacks including the induction of immune responses that reduce the success of repeated applications, the costs of production of GMO quality vectors and possibly fatal consequences due to the virulence of the approach (Raper et al 2003).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…[29] Using the same approach, it was demonstrated that detecting doping transgene in blood of nonhuman primates was possible. [25] Indeed, intramuscular injection of a conventional plasmid and rAAV vectors resulted in the presence of DNA that could be detected at high levels in blood and that rAAV genomes can persist for several months in WBCs.…”
Section: Detection Of Gene Dopingmentioning
confidence: 99%
“…[25] However, due to its high invasiveness, muscle biopsy would be impossible for sample harvesting. Direct injection into a target tissue has been considered as an approach which leads to entry of minutes amounts of transgenic DNA into the blood stream.…”
Section: Detection Of Gene Dopingmentioning
confidence: 99%
See 1 more Smart Citation